Diaphragm for sound production device, sound production device, and electronic device
Patent Information
- Application Number
- CN202610965952.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-30
- Publication Date
- 2026-10-16
AI Technical Summary
[0002]TWS耳机、头戴式耳机等设备搭载的微型扬声器振膜,受产品结构限制,需在狭小装配空间内实现高保真发声效果,同时终端产品应用工况复杂多样
[0017]This application uses an organo-montmorillonite and TPU blend composite system to prepare a diaphragm for a sound-generating device. The diaphragm includes at least one composite film, which includes a thermoplastic polyurethane base film and organo-montmorillonite dispersed in the thermoplastic polyurethane base film. The organo-montmorillonite accounts for 0.5wt%~30wt% of the mass of a single composite film. The organo-montmorillonite has a layered stacked structure with a (001) crystal plane interlayer spacing d001≥1.8nm. By controlling the addition ratio of organo-montmorillonite, the toughness deterioration and poor molding problems caused by filler agglomeration are avoided. At the same time, the interface enhancement and barrier effect of nano-layered silicate are fully utilized to resolve the inherent performance contradiction between the temperature resistance and oil resistance of traditional TPU, and significantly improve the dimensional and acoustic stability of the diaphragm under extreme use environments such as high and low temperatures and human body oil erosion.
Smart Images

Figure CN122934159A_ABST
Abstract
Description
Technical Field
[0001] This application belongs to the field of electroacoustic technology, and specifically relates to a diaphragm for a sound-generating device, a sound-generating device, and an electronic device. Background Technology
[0002] The miniature speaker diaphragms used in devices such as TWS earphones and over-ear headphones are constrained by product structure, requiring high-fidelity sound production within a limited assembly space. Furthermore, the operating conditions of these end products are complex and diverse. Existing traditional thermoplastic polyurethane materials used in diaphragm fabrication present several inherent performance contradictions: firstly, it's difficult to simultaneously achieve both low-temperature resistance and resistance to human oils and sweat; secondly, high-temperature stability and low-temperature mechanical properties cannot be balanced synchronously. These two types of properties mutually restrict each other, making it difficult to meet the needs of earphones in all usage scenarios. Therefore, existing speaker diaphragms still require improvement. Summary of the Invention
[0003] The purpose of this application is to provide a diaphragm for a sound-generating device, a sound-generating device, and an electronic device. The diaphragm for a sound-generating device provided by this application avoids the problems of toughness deterioration and poor molding caused by filler agglomeration by adding organic montmorillonite and controlling the amount added. At the same time, it fully utilizes the interface enhancement and barrier effect of nano-layered silicate to resolve the inherent performance contradiction between the temperature resistance and oil resistance of traditional TPU, and significantly improves the dimensional and acoustic stability of the diaphragm in extreme use environments such as high and low temperatures and human body oil corrosion.
[0004] The first aspect of this application provides a diaphragm for a sound-generating device, comprising at least one composite material film, the composite material film comprising a thermoplastic polyurethane base film and an organomontmorillonite dispersed within the thermoplastic polyurethane base film, the organomontmorillonite accounting for 0.5wt%~30wt% of the mass of a single layer of the composite material film, the organomontmorillonite having a layered stacked structure, the (001) crystal plane interlayer spacing d001 ≥ 1.8nm, and the oleic acid adsorption rate of a single layer of the composite material film ≤ 8%.
[0005] In some embodiments of this application, the chlorine element in the organomontmorillonite accounts for less than 0.09 wt% of the mass of the organomontmorillonite.
[0006] In some embodiments of this application, the bromine element in the organomontmorillonite accounts for less than 0.09 wt% of the mass of the organomontmorillonite.
[0007] In some embodiments of this application, the delamination rate of the organomontmorillonite is >50%.
[0008] In some embodiments of this application, the organomontmorillonite is prepared by modifying montmorillonite with at least one of halogen-free quaternary ammonium salts, imidazoles, and aminosilane coupling agents.
[0009] In some embodiments of this application, the glass transition temperature of the single-layer composite film is ≤-30°C.
[0010] In some embodiments of this application, the loss factor of a single-layer composite film at -20°C is ≥0.15.
[0011] In some embodiments of this application, the 3% relative change rate of the secant modulus of the single-layer composite film after 96 hours of damp heat aging at 65°C and 95%RH satisfies: ×100%≤10%; where, This indicates the 3% secant modulus of the composite film after 96 hours of damp heat aging at 65°C and 95%RH. This indicates the 3% secant modulus of the composite film before aging.
[0012] In some embodiments of this application, the rate of decrease in the storage modulus of the monolayer composite film at 55°C compared to that at 25°C satisfies: ×100%≤25%; where, This indicates the storage modulus of the composite film at 25°C. This indicates the storage modulus of the composite film at 55°C.
[0013] In some embodiments of this application, the diaphragm is formed as a composite layer structure, wherein the composite layer structure comprises at least two layers of the composite material film.
[0014] In some embodiments of this application, the composite layer structure further includes a composite connecting layer, which is stacked with the composite material film. The composite connecting layer is one or more of the following: polyurethane film, thermoplastic polyester elastomer film, polyetheretherketone film, silicone rubber film, acrylate rubber film, ethylene-acrylate rubber film, acrylic pressure-sensitive adhesive film, and organosilicon pressure-sensitive adhesive.
[0015] The second aspect of this application also provides a sound-generating device, which includes a diaphragm for the sound-generating device described in the first aspect of this application.
[0016] A third aspect of this application also provides an electronic device, which includes a diaphragm for a sound-generating device as described in the first aspect of this application or a sound-generating device as described in the second aspect of this application.
[0017] This application uses an organo-montmorillonite and TPU blend composite system to prepare a diaphragm for a sound-generating device. The diaphragm includes at least one composite film, which includes a thermoplastic polyurethane base film and organo-montmorillonite dispersed in the thermoplastic polyurethane base film. The organo-montmorillonite accounts for 0.5wt%~30wt% of the mass of a single composite film. The organo-montmorillonite has a layered stacked structure with a (001) crystal plane interlayer spacing d001≥1.8nm. By controlling the addition ratio of organo-montmorillonite, the toughness deterioration and poor molding problems caused by filler agglomeration are avoided. At the same time, the interface enhancement and barrier effect of nano-layered silicate are fully utilized to resolve the inherent performance contradiction between the temperature resistance and oil resistance of traditional TPU, and significantly improve the dimensional and acoustic stability of the diaphragm under extreme use environments such as high and low temperatures and human body oil erosion.
[0018] The above description is only an overview of the technical solution of this application. In order to better understand the technical means of this application and to implement it in accordance with the contents of the specification, and to make the above and other objects, features and advantages of this application more obvious and understandable, the following are specific embodiments of this application. Attached Figure Description
[0019] To more clearly illustrate the technical solutions in the specific embodiments of this application or the prior art, the drawings used in the description of the specific embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of this application. For those skilled in the art, other drawings can be obtained from these drawings without creative effort.
[0020] Figure 1 This is a schematic diagram of the structure of the sound-generating device in some embodiments of this application.
[0021] Explanation of reference numerals in the attached figures 100 - Sound-generating device; 10-Housing; 20-Diaphragm; 30-Voice coil; 40-Magnetic circuit system. Detailed Implementation
[0022] Exemplary embodiments of this application will now be described in more detail with reference to the accompanying drawings. While exemplary embodiments of this application are shown in the drawings, it should be understood that this application may be implemented in various forms and should not be limited to the embodiments set forth herein. Rather, these embodiments are provided to enable a more thorough understanding of this application and to fully convey the scope of this application to those skilled in the art.
[0023] It should be understood that the terminology used herein is for the purpose of describing particular exemplary embodiments only and is not intended to be limiting. Unless the context clearly indicates otherwise, the singular forms “a,” “an,” and “described” as used herein may also include the plural forms. The terms “comprising,” “including,” “containing,” and “having” are inclusive and therefore indicate the presence of the stated features, steps, operations, elements, and / or components, but do not exclude the presence or addition of one or more other features, steps, operations, elements, components, and / or combinations thereof. The method steps, processes, and operations described herein are not construed as requiring them to be performed in a particular order described or illustrated unless the order of performance is explicitly indicated. It should also be understood that additional or alternative steps may be used.
[0024] In the description of the embodiments of this application, technical terms such as "first" and "second" are used only to distinguish different objects and should not be construed as indicating or implying relative importance or implicitly specifying the number, specific order, or primary and secondary relationship of the indicated technical features. In the description of the embodiments of this application, "multiple" means two or more, unless otherwise explicitly defined.
[0025] In this document, the term "embodiment" means that a particular feature, structure, or characteristic described in connection with an embodiment may be included in at least one embodiment of this application. The appearance of this phrase in various places throughout the specification does not necessarily refer to the same embodiment, nor is it a separate or alternative embodiment mutually exclusive with other embodiments. It will be explicitly and implicitly understood by those skilled in the art that the embodiments described herein can be combined with other embodiments.
[0026] In the description of the embodiments in this application, the term "and / or" is merely a description of the relationship between related objects, indicating that three relationships can exist. For example, A and / or B can represent: A existing alone, A and B existing simultaneously, and B existing alone. Additionally, the character " / " in this document generally indicates that the preceding and following related objects have an "or" relationship.
[0027] In the description of the embodiments of this application, the term "multiple" refers to two or more (including two), similarly, "multiple sets" refers to two or more (including two sets), and "multiple pieces" refers to two or more (including two pieces).
[0028] The first aspect of this application provides a diaphragm for a sound-generating device, the diaphragm comprising at least one composite material film, the composite material film comprising a thermoplastic polyurethane base film and an organomontmorillonite dispersed within the thermoplastic polyurethane base film, the organomontmorillonite accounting for 0.5wt% to 30wt% of the mass of a single layer of the composite material film, the organomontmorillonite having a layered stacked structure, and its (001) interlayer spacing d 001The oleic acid adsorption rate of a single-layer composite film is ≤8% with a wavelength of ≥1.8nm.
[0029] In the embodiments of this application, a diaphragm for a sound-generating device is prepared by using an organo-montmorillonite and TPU blend composite system. By controlling the addition ratio of organo-montmorillonite, the toughness deterioration and poor molding caused by filler agglomeration are avoided. At the same time, the interface enhancement and barrier effect of nano-layered silicate is fully utilized to resolve the inherent performance contradiction between the temperature resistance and oil resistance of traditional TPU, and significantly improve the dimensional and acoustic stability of the diaphragm under extreme usage environments such as high and low temperatures and human body oil erosion.
[0030] Specifically, organomontmorillonite (OMMT) is a layered silicate filler that can be dissociated into a nanoscale sheet structure after organic intercalation modification. It can be uniformly dispersed in the TPU matrix and form a high-strength interfacial bond. This can simultaneously optimize the high and low temperature resistance of the substrate and form a dense barrier layer to prevent the penetration of media such as oil and sweat, thereby improving the shortcomings of TPU in temperature resistance and oil resistance from the root.
[0031] Unmodified natural montmorillonite flakes exhibit strong electrostatic and hydrogen bonding interactions between their layers, resulting in extremely poor interfacial compatibility with the TPU polymer matrix. This leads to severe aggregation in blended systems, ultimately degrading the overall performance of the diaphragm. Furthermore, the tightly packed layers of natural montmorillonite, with an interlayer spacing of only about 1 nm, prevent the diffusion and intercalation of TPU polymer chains, hindering their ability to provide nano-reinforcement and barrier modification, resulting in a weak nano-effect. The interlayer spacing d of organic montmorillonite... 001 Controlling the nanoparticle size to 1.8 nm or higher ensures smooth insertion of polymer chain segments into the interlayer, reduces filler agglomeration, and fully leverages the modification and gain of the TPU diaphragm by the nanofiller. Furthermore, when the interlayer spacing d of the organomontmorillonite is... 001 At a thickness <1.8 nm, the interlayer extension after modification is still insufficient, the interlayer forces are not sufficiently weakened, and the filler is still prone to stacking and agglomeration during processing, making effective nano-exfoliation impossible and significantly reducing the reinforcement and barrier effects. (Interlayer spacing d) 001 The larger the value of d, the more complete the organic intercalation modification, and the easier it is for the sheets to peel and disperse under external force and shear. 001 When the thickness is greater than 3nm, the montmorillonite sheets can be fully expanded and dissociated into single-layer or 2 to 5-layer nanostructures in the TPU matrix. This significantly increases the effective specific surface area of the filler, improves stress transfer efficiency, and fully releases the modification effects such as nano-reinforcement and oil and water vapor barrier.
[0032] In some embodiments of this application, the interlayer spacing d 001 The interlayer spacing can range from 1.8 nm to 4 nm. As an example, the interlayer spacing d of organomontmorillonite... 001It can be one of 1.8nm, 1.9nm, 2nm, 2.2nm, 2.5nm, 2.5nm, 2.6nm, 2.7nm, 2.8nm, 2.9nm, 3nm, 3.5nm, 4nm or any value that satisfies the above range.
[0033] The percentage of organo-montmorillonite in a single-layer composite film ranges from 0.5 wt% to 30 wt%. Understandably, when the organo-montmorillonite content is below 0.5 wt%, the overall content is too low, making it difficult to disperse uniformly in the TPU matrix and form a continuous and effective nanosheet network. This hinders its ability to provide nano-reinforcement, modulus enhancement, and physical barrier properties. Conversely, when the organo-montmorillonite content exceeds 30 wt%, the excessive proportion leads to severe lamellar agglomeration, significantly reducing the interlayer peeling efficiency. The original nanoscale lamellars transform into micron-sized agglomerated particles, directly causing a significant deterioration in the tensile strength, elongation at break, and other mechanical properties of the composite film. Simultaneously, the melt viscosity increases sharply, fluidity deteriorates drastically, and thermoplastic molding processing performance is lost. Therefore, limiting the organo-montmorillonite percentage to the range of 0.5 wt% to 30 wt% ensures sufficient peeling and uniform dispersion, stably achieving multiple effects such as nano-reinforcement, improved temperature resistance, and grease barrier properties, while also considering material toughness and melt processing performance. In some embodiments of this application, the organomontmorillonite constitutes a mass percentage of 1 wt% to 25 wt% of the single-layer composite film. Exemplarily, the mass percentage of organomontmorillonite in the single-layer composite film can be one of 0.5 wt%, 0.8 wt%, 1 wt%, 2 wt%, 3 wt%, 4 wt%, 5 wt%, 6 wt%, 7 wt%, 8 wt%, 9 wt%, 10 wt%, 11 wt%, 12 wt%, 13 wt%, 14 wt%, 15 wt%, 16 wt%, 17 wt%, 18 wt%, 19 wt%, 20 wt%, 21 wt%, 22 wt%, 23 wt%, 24 wt%, 25 wt%, 26 wt%, 27 wt%, 28 wt%, 29 wt%, or 30 wt%, or any value satisfying the above range.
[0034] In the embodiments of this application, the oleic acid adsorption rate of the single-layer composite film is ≤8%. It is understood that oleic acid has the molecular formula C0. 18 H 34O2, an unsaturated fatty acid, is the most representative component of human ear canal oils. The industry often uses oleic acid as an artificial simulated ear fat to conduct oil erosion resistance tests. Based on the principle of "like dissolves like," oleic acid molecules are small in size and can easily penetrate into the gaps between polymer chain segments, causing irreversible damage to the diaphragm: after oleic acid penetrates into the TPU matrix, it widens the gaps between molecular chains, weakens the intermolecular forces, and causes a significant decrease in the material modulus and softening and failure of the diaphragm; at the same time, oleic acid can activate polymer chain segments, causing the chain segments to relax freely and release a large amount of internal stress, resulting in disordered deformation of the diaphragm surface texture and molding pattern, and impairing the acoustic structural stability.
[0035] In this application system, the addition of organo-montmorillonite allows for the construction of a dense nano-barrier network within the base membrane, preventing oleic acid from penetrating deep into the membrane. Simultaneously, the continuous layered network effectively bears stress transmission. Therefore, organo-montmorillonite-reinforced TPU membranes exhibit superior resistance to ear canal grease erosion compared to pure TPU membranes, thereby controlling the oleic acid adsorption rate of the composite film to below 8%. This significantly reduces oleic acid wetting and diffusion, ensuring stable diaphragm mechanical properties, appearance, and acoustic performance over long-term use. For example, the oleic acid adsorption rate of the composite film can be one of 8%, 7%, 6%, 5%, 4.3%, 4%, 3.8%, 3.7%, 3%, 2%, or 1%, or any value within the aforementioned range.
[0036] In some embodiments of this application, organomontmorillonite is prepared by modifying montmorillonite with at least one of halogen-free quaternary ammonium salts, imidazoles, and aminosilane coupling agents.
[0037] Existing montmorillonite fillers have significant limitations. They are prone to lamellar aggregation, which directly leads to a significant decrease in the elongation at break and toughness of the composite membrane. During the molding process, pinholes, uneven thickness, and other appearance and molding defects are generated, which cannot meet the standards for thin, highly elastic, and acoustically stable diaphragms used in sound-generating devices.
[0038] In this embodiment, montmorillonite is modified using halogen-free quaternary ammonium salts, etc., and the Na+ and Ca+ in the interlayer of montmorillonite are replaced by an "ion exchange reaction". 2+ Inorganic cations can both widen the interlayer spacing, providing a prerequisite for polymer entry, and improve the compatibility between montmorillonite and polymers. The cation exchange capacity of montmorillonite itself directly determines the modification effect: when the cation exchange capacity is high, it can carry more organic modifiers, resulting in a higher organic loading, stronger hydrophobicity, larger interlayer spacing, and easier exfoliation and dispersion in the matrix after modification; if the cation exchange capacity is low, the organic modifier loading is insufficient, the degree of montmorillonite modification is insufficient, the layers are difficult to completely dissociate, and ultimately the filler's dispersion in the TPU matrix becomes poor, failing to fully exert its nano-reinforcement and barrier effects.
[0039] In some embodiments of this application, the chlorine element in the organomontmorillonite accounts for less than 0.09 wt% of the mass of the organomontmorillonite.
[0040] In some embodiments of this application, the bromine content in the organomontmorillonite is <0.09 wt%.
[0041] The organomontmorillonite used in this application must have strictly controlled halogen content, requiring that the mass fraction of chlorine be <0.09wt% and / or the mass fraction of bromine be <0.09wt%. According to IEC 61249-2-21 and IPC-4101B halogen-free standards for the electronics industry, the control limits for hazardous substances in composite materials for electronic components are: chlorine (Cl) content <900ppm, bromine (Br) content <900ppm, and total chlorine and bromine content <1500ppm. When the mass percentage of chlorine or bromine in organo-montmorillonite is ≥0.09wt%, two core defects exist: First, the halogen content exceeds the standard, and the resulting diaphragm cannot pass the halogen-free test of IEC 61249 2 21 and IPC 4101B, making it unsuitable for compliant products such as consumer electronics and acoustic devices. Under high-temperature conditions, the material is also prone to releasing halogen-containing harmful substances, corroding speaker metal components, and posing environmental and safety hazards. Second, the large amount of halogen residue in the modifier reduces the interfacial compatibility between organo-montmorillonite and the TPU matrix, exacerbates the problem of uneven filler dispersion and local agglomeration, weakens the nano-reinforcement and media barrier effects, and deteriorates the diaphragm's mechanical and weather resistance properties. Therefore, controlling the mass percentage of chlorine and bromine in organo-montmorillonite below 0.09wt% ensures that the individual chlorine and bromine content, as well as the total halogen content, in the final composite film falls within the halogen-free standard control range, balancing the environmental compliance requirements of the electronics industry with the effects of filler modification, dispersion, and enhanced barrier properties.
[0042] As an example, the mass percentage of chlorine in organomontmorillonite can be one of 0.09 wt%, 0.08 wt%, 0.07 wt%, 0.06 wt%, 0.05 wt%, 0.04 wt%, 0.02 wt%, or 0.01 wt%, or any value within the range mentioned above. As an example, the mass percentage of bromine in organomontmorillonite can be one of 0.09 wt%, 0.08 wt%, 0.07 wt%, 0.06 wt%, 0.05 wt%, 0.04 wt%, 0.02 wt%, or 0.01 wt%, or any value within the range mentioned above.
[0043] The industry commonly uses hexadecyltrimethylammonium bromide as an organic modifier for montmorillonite, with the molecular formula C632. 19 H 42BrN has a theoretical bromine content as high as 21.9 wt%. Taking sodium-based montmorillonite with a cation exchange capacity of 60 mmol / 100g as an example, after complete ion exchange modification with cetyltrimethylammonium bromide with a cation exchange equivalent, the resulting organomontmorillonite can reach a bromine content of 3 wt%. If this high-bromine organomontmorillonite is applied to a TPU diaphragm system, even with only 3 wt% of organomontmorillonite added, the overall bromine content of the composite material will exceed the halogen-free standard limit, failing to meet the halogen-free usage specifications for electronic components such as headphone miniature speakers.
[0044] In some embodiments of this application, the delamination rate of organomontmorillonite is >50%. It is understood that the delamination rate of organomontmorillonite is defined as the percentage of single-layer and 2-5 layer organomontmorillonite flakes to the total number of flakes. When the delamination rate of organomontmorillonite is less than 50%, it means that the organomontmorillonite flakes are mostly present in a multi-layered, agglomerated state, unable to be fully dissociated and dispersed in the TPU matrix. This will have multiple negative impacts on the overall performance of the diaphragm, resulting in insufficient improvement in diaphragm modulus, poor barrier properties, poor processability, and decreased light transmittance. Exemplarily, the delamination rate of organomontmorillonite can be one of 51%, 52%, 53%, 54%, or 55%, or any value within the above range.
[0045] In some embodiments of this application, the test and statistical method for the peeling rate of organomontmorillonite is as follows: obtain microscopic morphology photos of the material by SEM or TEM microscopic observation, count the peeled and dispersed few-layered monomers and the incompletely peeled stacked agglomerates, calculate the peeling rate by area ratio method, and the number of samples in a single statistical analysis is not less than 200 to ensure that the test data is accurate and reliable.
[0046] In some embodiments of this application, the glass transition temperature of the single-layer composite film is ≤-30℃. It is understood that the industry standard for low-temperature performance testing of sound-generating devices is -20℃, and the vibration characteristics of the diaphragm play a decisive role in low-frequency sound production. Furthermore, the actual operating frequency of the sound-generating device is higher than the standard low-temperature test frequency. Based on the time-temperature equivalence principle, the diaphragm's glass transition temperature needs to be controlled at -30℃ or lower to ensure stable vibration under low-temperature conditions. However, if the diaphragm's glass transition temperature is higher than -30℃, in the actual use environment of -20℃, the diaphragm is prone to entering the glassy state, resulting in a sharp increase in elastic modulus, increased material hardening and brittleness, directly causing two major adverse consequences: first, the diaphragm's resonant frequency shifts to higher frequencies, distorting the acoustic curve; second, the membrane's vibration flexibility is significantly reduced, deteriorating low-frequency sound production performance and failing to meet the high-fidelity sound production requirements of the sound-generating device in low-temperature environments. For example, the glass transition temperature of the composite film can be one of -30°C, -35°C, -40°C, -45°C, -47°C, -48°C, -50°C, or any value that satisfies the above range.
[0047] In some embodiments of this application, the loss factor of the single-layer composite film at -20°C is ≥0.15. It is understood that organomontmorillonite relies on interfacial stick-slip and lamellar shear to form a synergistic energy dissipation network: nanosheets form reversible hydrogen bonds with polyurethane, constraining the molecular chains under alternating stress, generating viscoelastic hysteresis loss; the exfoliated lamellar vibration slips, and the modifier increases interlayer friction, converting vibrational mechanical energy into heat dissipation. This suppresses the split vibration start frequency, reduces the resonant Q value, and suppresses standing waves and distortion; thus, the sound output exhibits a clean transient response and a flat frequency response, resulting in a high-fidelity acoustic output. Therefore, the loss factor of the single-layer composite film at -20°C can be ≥0.15, exhibiting high damping performance. Exemplarily, the loss factor of the composite film at -20°C can be one of 0.15, 0.16, 0.17, 0.18, 0.19, 0.2, 0.241, 0.271, 0.297, or any value satisfying the above range.
[0048] In some embodiments of this application, the 3% relative change rate of the secant modulus of the single-layer composite film after 96 hours of damp heat aging at 65°C and 95%RH satisfies: ×100%≤10%; where, This indicates the 3% secant modulus of the composite film after 96 hours of damp heat aging at 65°C and 95%RH. This indicates the 3% secant modulus of the composite film before aging.
[0049] Organic montmorillonite is a two-dimensional sheet filler randomly dispersed within the TPU base film. When water vapor permeates and diffuses into the material, it must bypass the impermeable montmorillonite sheets, significantly extending the water vapor diffusion path and creating an excellent physical barrier against water vapor, reducing performance degradation caused by the intrusion of humid heat media into the diaphragm. Simultaneously, once the organic montmorillonite filler reaches the permeation threshold, the overlapping organic montmorillonite sheets form a continuous stress transfer network, which can share external loads and effectively compensate for the 3% secant modulus loss that occurs in the polymer matrix itself after humid heat aging, maintaining the diaphragm's rigidity and stability. However, when the relative change rate of the 3% secant modulus after humid heat aging exceeds 10%, it indicates insufficient resistance to humid heat aging: a large amount of water vapor intrudes into the matrix, disrupting the intermolecular forces of TPU, resulting in a significant decrease in modulus and a marked reduction in diaphragm rigidity; under long-term high-temperature and high-humidity conditions, the diaphragm is prone to deformation, resonant frequency drift, intensified split vibration, and increased distortion, making it impossible to consistently output high-fidelity sound quality. For example, the relative change rate of the 3% secant modulus of the composite film after aging at 65°C and 95%RH for 96 hours can be one of 10%, 9%, 8%, 7%, 6%, 5%, 4%, 3%, 2%, 1% or any value that meets the above range.
[0050] In some embodiments of this application, the rate of decrease in the storage modulus of the single-layer composite film at 55°C compared to that at 25°C satisfies: ×100%≤25%; where, This indicates the storage modulus of the composite film at 25°C. This indicates the storage modulus of the composite film at 55°C.
[0051] Understandably, 55℃ is the high-temperature test temperature for simulating high-power, long-term continuous playback of a sound-generating device, used to verify the long-term high-temperature stability of the diaphragm. When the storage modulus of the composite film at 55℃ decreases by more than 25% compared to that at 25℃, the diaphragm experiences a significant decrease in rigidity and softening under high-temperature conditions, resulting in a severe lack of stiffness. During large-amplitude reciprocating vibrations, the diaphragm is highly susceptible to fatigue damage and irreversible permanent deformation. Even if the operating temperature subsequently drops to room temperature, the diaphragm size and vibration pattern cannot return to their original state, causing a continuous shift in resonant frequency, increased acoustic distortion, and an inability to achieve stable sound production over a long period. In this application, the organic montmorillonite layer network can maintain load transfer capability at high temperatures, suppress the sudden drop in modulus caused by thermal relaxation of polymer chain segments, and control the decrease in storage modulus of the composite film at 55℃ compared to that at 25℃ to within 25%, ensuring stable diaphragm rigidity and excellent resistance to deformation under high-power, long-term playback conditions. For example, the rate of decrease in the storage modulus of the composite film at 55°C compared to that at 25°C can be one of 25%, 22%, 20%, 18%, 15%, 13%, 12%, 10%, 9%, 8%, 7%, 6%, 5%, 4%, 3%, 2%, 1% or any value satisfying the above range.
[0052] In some embodiments of this application, the hardness of the single-layer composite film is 70A to 98A. It is understood that if the diaphragm hardness is too low, below 70A, resonance and segmentation vibration will occur, leading to distortion; to avoid this defect, a high-thickness film is required, which will occupy cavity space. Conversely, if the diaphragm hardness is too high, above 98A, the low frequencies will be weak and lack extension, and the mid-frequency response will be poor, requiring a low-thickness film. Hardness exceeding a reasonable range will deteriorate the sound performance. Exemplarily, the hardness of the composite film can be one of 70A, 72A, 75A, 78A, 80A, 82A, 85A, 88A, 90A, 92A, 95A, or 98A, or any value satisfying the above range.
[0053] In some embodiments of this application, the thermoplastic polyurethane base film (thermoplastic polyurethane) is composed of hard segments and soft segments. The soft segments impart good flexibility to the polymer material, giving it superior low-temperature resistance; the hard segments impart higher rigidity to the polymer material, giving it better heat resistance. The hard segments can be urethane (-NH-COO-) and / or urea bond (-NH-CO-NH-) segments formed by the reaction of diisocyanate with a small molecule chain extender, and the soft segments can be at least one of polyether polyol, polyester polyol, and polycarbonate polyol.
[0054] In some embodiments of this application, the diaphragm is formed as a composite layer structure, wherein the composite layer structure includes at least two composite material films, each composite material film comprising a thermoplastic polyurethane base film and an organomontmorillonite dispersed within the thermoplastic polyurethane base film. It is understood that the diaphragm of the composite layer structure contains at least two composite material films, each composite material film being formed by blending and processing a material containing urethane bonds (-NH-COO-) and / or urea bonds (-NH-CO-NH-) of thermoplastic polyurethane and organomontmorillonite. In some embodiments of this application, the two or more composite material films are stacked.
[0055] In some embodiments of this application, the diaphragm is formed as a composite layer structure, wherein the composite layer structure includes a composite material film and a composite connecting layer, the composite connecting layer and the composite material film are stacked together, the composite material film includes a thermoplastic polyurethane base film and an organomontmorillonite dispersed in the thermoplastic polyurethane base film, and the composite connecting layer can be one or more of the following: polyurethane film, thermoplastic polyester elastomer film, polyetheretherketone film, silicone rubber film, acrylate rubber film, ethylene-acrylate rubber film, acrylic pressure-sensitive adhesive film, and organosilicon pressure-sensitive adhesive.
[0056] The second aspect of this application provides a sound-generating device, which includes a diaphragm for the sound-generating device described in the first aspect of this application.
[0057] In some embodiments of this application, the sound-generating device may be a loudspeaker, such as a miniature loudspeaker. Figure 1 As shown, the sound-generating device 100 of this application includes a housing 10, a vibration system disposed within the housing 10, and a magnetic circuit system 40 cooperating with the vibration system. The vibration system includes a diaphragm 20 and a voice coil 30 coupled to one side of the diaphragm 20. The magnetic circuit system 40 drives the voice coil 30 to vibrate, thereby causing the diaphragm 20 to produce sound. When the sound-generating device 100 is working, an electrical signal is input to the voice coil 30. The voice coil 30 is driven by the magnetic field force of the magnetic circuit system 40 and moves with different amplitudes and directions as the signal magnitude and positive and negative directions alternate, thereby causing the diaphragm 20 to vibrate and produce sound, thus completing the process of converting electrical energy into mechanical energy into sound energy.
[0058] A third aspect of this application provides an electronic device that includes a diaphragm for a sound-generating device as described in the first aspect of this application or a sound-generating device as described in the second aspect of this application.
[0059] In the embodiments of this application, the electronic device may be, but is not limited to, a mobile phone, a tablet computer, a smartwatch, a game console, a learning machine, etc., and the electronic device has the characteristic of good acoustic effect.
[0060] Unless otherwise defined, the technical terms used in the following embodiments have the same meaning as commonly understood by those skilled in the art to which this application pertains. Unless otherwise specified, the experimental reagents used in the following embodiments are all conventional biochemical reagents; the raw materials, instruments, and equipment used in the following embodiments can all be obtained through commercial purchase or by existing methods; the amounts of experimental reagents used are, unless otherwise specified, the amounts used in conventional experimental operations; and the experimental methods used are, unless otherwise specified, conventional methods. It should be further noted that the following descriptions are merely exemplary and not intended to limit the scope of this application. Moreover, the comparative examples below are selected to compare with the technical solutions of this application to demonstrate the advancement of the technical solutions of this application, and do not necessarily represent prior art in this technical field.
[0061] Example 1 Embodiment 1 of this application provides a loudspeaker diaphragm, which is a single-layer composite film made of a thermoplastic polyurethane base film with organomontmorillonite dispersed internally. The organomontmorillonite (OMMT) accounts for 4 wt% of the mass of the single-layer composite film, and the thermoplastic polyurethane base film accounts for 96 wt% of the mass. The thermoplastic polyurethane is a polyester-type TPU with a hardness of 75A and a glass transition temperature (Tg) of -50°C. The interlayer spacing d of the organomontmorillonite (001) crystal planes is also described. 001 The particle size is 2.8 nm, the peeling rate is 75%, and the particle size D50 is 8 μm.
[0062] Performance testing 1. Energy storage modulus change rate test.
[0063] Dynamic thermomechanical analyzer was used, according to ASTM D5026-23 standard, in tensile mode, at a frequency of 1 Hz and a strain of 0.5%.
[0064] 2.3% secant modulus test.
[0065] Using a universal tensile testing machine, in accordance with ASTM D882 standard, the preload force was 0.1N, the specimen width was 15mm, the clamp spacing was 30mm, and the tensile rate was 300mm / min.
[0066] 3. Glass transition temperature test.
[0067] Referring to GB / T 19466.1-2004 standard, the test temperature was -80℃ to 220℃, the heating rate was 20℃ / min, and the glass transition temperature was determined using the half-height method.
[0068] 4. -20℃ loss factor test.
[0069] According to ASTM D5026 standard, the heating rate is 3℃ / min, the strain is 0.5%, the test temperature range is -60℃ to 150℃, the tensile mode is used, and the damping factor value is read under the condition of -20℃.
[0070] The diaphragm in Example 1 was subjected to the corresponding performance tests according to the above test methods, and the test results are summarized in Table 1.
[0071] The miniature loudspeaker obtained by assembling the diaphragm in Example 1 was used for corresponding performance tests.
[0072] Example 2 The only difference between Example 2 and Example 1 is that the modified kaolin accounts for 0.5 wt% of the elastomer film. The rest of the preparation and testing methods are the same as in Example 1, and the test results are summarized in Table 1.
[0073] Example 3 The only difference between Example 3 and Example 1 is that the modified kaolin accounts for 1 wt% of the elastomer film. The rest of the preparation and testing methods are the same as in Example 1, and the test results are summarized in Table 1.
[0074] Example 4 The only difference between Example 4 and Example 1 is that the modified kaolin accounts for 15 wt% of the elastomer film. The rest of the preparation and testing methods are the same as in Example 1, and the test results are summarized in Table 1.
[0075] Example 5 The only difference between Example 5 and Example 1 is that the modified kaolin accounts for 25 wt% of the elastomer film. The rest of the preparation and testing methods are the same as in Example 1, and the test results are summarized in Table 1.
[0076] Example 6 The only difference between Example 6 and Example 1 is that the modified kaolin accounts for 30 wt% of the elastomer film. The rest of the preparation and testing methods are the same as in Example 1, and the test results are summarized in Table 1.
[0077] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that the diaphragm used in Comparative Example 1 is a commercially available polyester TPU with a hardness of 90A. All other tests were conducted using the same methods as in Example 1, and the test results are summarized in Table 1.
[0078] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that the diaphragm used is a commercially available polyether-type TPU with a hardness of 81A. All other tests were conducted using the same methods as in Example 1, and the test results are summarized in Table 1.
[0079] Comparative Example 3 The only difference between Comparative Example 3 and Example 1 is that unmodified montmorillonite with a particle size D50 of 10 μm was used; the mass percentage of montmorillonite in the single-layer composite film was 25 wt%, and the mass percentage of the thermoplastic polyurethane base film was 75 wt%. The rest of the preparation and testing methods were the same as in Example 1, and the test results are summarized in Table 1.
[0080] Comparative Example 4 The only difference between Comparative Example 4 and Example 1 is that the organomontmorillonite accounts for 31 wt% of the composite film. The rest of the preparation and testing methods were the same as in Example 1, and the test results are summarized in Table 1.
[0081] Comparative Example 5 The only difference between Comparative Example 5 and Example 1 is that the organomontmorillonite accounts for 0.4 wt% of the composite film mass. The rest of the preparation and testing methods were the same as in Example 1, and the test results are summarized in Table 1.
[0082] Table 1
[0083] As can be seen from the test results in Table 1, the organomontmorillonite in Example 1 of this application can play a physical barrier role, and oleic acid diffusion needs to bypass the organomontmorillonite, thus extending the diffusion path. In contrast, in Comparative Example 3, the poor bonding force between montmorillonite and TPU, and the weak interface, actually provides a pathway for oleic acid diffusion. In Example 1, due to the good damping at -20℃, the EQ voltage polarization is not obvious in the low-temperature environment, resulting in better sound quality. However, in Comparative Example 3, the polarization can reach over 0.8mm, leading to poorer sound quality; the low damping causes the polarization to bottom out at the Q value, resulting in rubbing sounds.
[0084] In Comparative Example 1, F0 exhibits poor stability. It has a low glass transition temperature and poor stability at low temperatures; the temperature range of F0 is large from 25℃ to 55℃ / 95%RH, and its acoustic performance degrades in high-temperature and high-humidity environments.
[0085] In Comparative Example 4, the amount of organomontmorillonite added was too high. Production stability was poor, with frequent melt instability and film breakage during production; the melt viscosity was too high, resulting in high melt pressure, making production difficult, and causing severe equipment wear.
[0086] In Comparative Example 5, the amount of organomontmorillonite added was too low. It did not reach the percolation threshold, failed to form an organomontmorillonite network, and had a poor loss factor.
[0087] Compared to other solutions, Comparative Example 2 showed a higher oleic acid adsorption capacity. Oleic acid penetration led to increased molecular chain spacing, material volume expansion, and distortion of the diaphragm geometry, deviating from the design. Acoustic performance deteriorated, exhibiting phenomena such as FR curve shift, decreased low-frequency F0, and intensified high-frequency segmentation vibration; mechanical failures occurred, including ring wrinkling and dome collapse, with some products experiencing direct diaphragm rupture in severe cases.
[0088] For TPU, the oleic acid adsorption rate is mainly related to two factors: First, the type of soft segment. Polyether-type TPU has weak molecular polarity, with van der Waals forces dominating intermolecular forces. Oleic acid easily penetrates into the inter-chain spaces through the principle of "like dissolves like," resulting in a high adsorption rate. Polyester-type TPU is more polar, with hydrogen bonds and dipole interactions existing between molecules. This strong polar structure effectively blocks the penetration of oleic acid. Second, the TPU's hardness (modulus). Increased TPU hardness leads to higher hardness ratios and crystallinity, restricting molecular chain movement; increased hardness also increases the number of urethane polar groups.
[0089] Compared to Example 1, Comparative Example 2 has significant drawbacks. The film thickness is high, resulting in a higher areal density. In terms of film fabrication, the high thickness makes film preparation difficult (poor film flatness, easy curling, and high shrinkage rate: this is due to uneven cooling shrinkage; the film is not significantly constrained by the release film before peeling, but curling and shrinking begin immediately upon peeling). Acoustically, the mid-frequency sensitivity is low, with a 0.5 dB decrease in sound pressure level; high-frequency extension deteriorates; third harmonic distortion increases; and loud volume becomes muddy, with reduced distortion margin (1. Increased thickness increases Mms in the Ts parameter; 2. Under the same voltage, vibration displacement is small, and vibration velocity is low; 3. Segmented vibration modes occur earlier, and high frequencies are no longer complete piston motion but become localized segmented resonance). In terms of molding, molding is difficult (to achieve effective high-performance, high-relief ring designs, higher molding temperatures are required, and the film stress uniformity decreases. Furthermore, the increased molding temperature leads to increased material fluidity during molding, causing elastomer to flow into the steel ring and mold base, affecting appearance, sound quality, and reliability).
[0090] Under high temperature and high humidity (55℃ / 95%RH) test conditions, the decrease in F0 in the examples and comparative examples corresponds to the decrease rate of energy storage modulus (from 25℃ to 55℃). The reason is as follows: Organo-montmorillonite sheets encapsulate and bind soft segment molecular chains, constraining the thermal rotation and extension of flexible chains. Uniformly dispersed organo-montmorillonite nanosheets constrain hard segment enrichment regions, preventing the collapse of hard segment micro-regions at high temperatures and maintaining the stability of the microphase separation structure. The modulus is mainly borne by the hardness micro-regions and the organo-montmorillonite. While polymers have poor heat resistance, organo-montmorillonite sheets exhibit extremely high heat resistance, with no effect on the inorganic framework at 55℃, thus suppressing the overall macroscopic modulus decay of the material. In contrast, montmorillonite, due to its poor interfacial bonding, is prone to interfacial slippage with the matrix, resulting in a rapid decrease in modulus.
[0091] In the implementation scheme of this application, by adding organic montmorillonite and controlling the amount added, the problems of toughness deterioration and poor molding caused by filler agglomeration are avoided. At the same time, the interface enhancement and barrier effect of nano-layered silicate is fully utilized to resolve the inherent performance contradiction between the temperature resistance and oil resistance of traditional TPU, and significantly improve the dimensional and acoustic stability of the diaphragm in extreme use environments such as high and low temperatures and human body oil erosion.
[0092] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of this application, and are not intended to limit them. Although this application has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features therein. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of this application.
Claims
1. A diaphragm for a sound-generating device, characterized in that, The composite film comprises at least one layer, the composite film comprising a thermoplastic polyurethane base film and an organo-montmorillonite dispersed within the thermoplastic polyurethane base film, wherein the organo-montmorillonite accounts for 0.5 wt% to 30 wt% of the mass of a single layer of the composite film. The organomontmorillonite has a layered stacked structure with a (001) interlayer spacing d. 001 ≥1.8nm, the oleic acid adsorption rate of a single layer of the composite material film is ≤8%.
2. The diaphragm for a sound-generating device as described in claim 1, characterized in that, In the organomontmorillonite, the chlorine element accounts for less than 0.09 wt% of the total mass of the organomontmorillonite. And / or, the bromine content is <0.09 wt% of the total mass of the organomontmorillonite.
3. The diaphragm for a sound-generating device as described in claim 1, characterized in that, The delamination rate of the organomontmorillonite is >50%.
4. The diaphragm for a sound-generating device as described in claim 1, characterized in that, The organomontmorillonite is prepared by modifying montmorillonite with at least one of halogen-free quaternary ammonium salts, imidazoles, and aminosilane coupling agents.
5. The diaphragm for a sound-generating device as described in claim 1, characterized in that, The glass transition temperature of a single-layer composite film is ≤-30℃; And / or, the loss factor of a single-layer composite film is ≥0.15 at -20°C.
6. The diaphragm for a sound-generating device as described in claim 1, characterized in that, The relative change rate of the 3% secant modulus of the single-layer composite film after 96 hours of damp heat aging at 65°C and 95%RH satisfies the following: ×100%≤10%; where, This indicates the 3% secant modulus of the composite film after 96 hours of damp heat aging at 65°C and 95%RH. This indicates the 3% secant modulus of the composite film before aging.
7. The diaphragm for a sound-generating device as described in claim 1, characterized in that, The rate of decrease in storage modulus of the single-layer composite film at 55°C compared to that at 25°C satisfies: ×100%≤25%; where, This indicates the storage modulus of the composite film at 25°C. This indicates the storage modulus of the composite film at 55°C.
8. The diaphragm for a sound-generating device as described in claim 1, characterized in that, The diaphragm is formed as a composite layer structure, wherein, The composite layer structure includes at least two layers of the composite material film; And / or, the composite layer structure further includes a composite connecting layer, which is stacked with the composite material film. The composite connecting layer is one or more of the following: polyurethane film, thermoplastic polyester elastomer film, polyetheretherketone film, silicone rubber film, acrylate rubber film, ethylene-acrylate rubber film, acrylic pressure-sensitive adhesive film, and organosilicon pressure-sensitive adhesive.
9. A sound-generating device, characterized in that, The diaphragm for the sound-generating device as described in any one of claims 1 to 8.
10. An electronic device, characterized in that, The diaphragm for the sound-generating device according to any one of claims 1 to 8, or the sound-generating device according to claim 9.